Nördliche Badia, Jordanien: Aride Lebensräume im 5. bis frühen 3. Jahrtausend v. Chr.: Mobile Subsistenz, Kommunikation und Ressourcennutzung - Müller-Neuhof, Bern (e-Forschungsberichte des DAI, 2023)
The Northern Badia is part of the greater steppe desert Badiyat ash-Sham centrally located between the Middle Euphrates and the Southern Levant. In Jordanian territory this steppe desert is differentiated into a basalt steppe desert (al-harra) and the eastern adjacent limestone steppe desert (al-hamad). The chronological focus of the research project lies on the Late Chalcolithic and Early Bronze Age period (5th to early 3rd millennium BC). This is a crucial period in the late prehistory of southwest Asia due to the fact that the first complex and urban societies, which were embedded in supra-regional networks, developed in Mesopotamia, Syria and Southern Levant, which are neighbouring the Northern Badia. The aim of the project is to investigate the impact of these developments on the socio-economy of the centrally located but arid Northern Badia. From spring 2010 to autumn 2011 several archaeological survey campaigns have been carried out in this region. In spring 2012 and 2013 two further survey campaigns have been executed as well as an analysing season in autumn 2012.